Application of Nursing Interventions in Patients with Pulmonary TB in Family Nursing Care in the Work Area of the Gorontalo District Health Center - Firmawati Firmawati; Andi Nur Aina Sudirman (Journal of Community Health Provision, 2022)
Tuberculosis has been an emerging threat in health of people that cause morbidity, disability, even increase the high number of deaths. So, it is necessary to find out the way to overcome it. Providing family nursing care, as one of health care interventions, is one of the best solutions to treat the patients with pulmonary tuberculosis. The aim of this research is to find out the implementation of health care interventions in patients with pulmonary tuberculosis at Comunity Health Centers of Gorontalo Regency. This has been running with the government’s program ‘Healthy Indonesia with Family Approach (PIS-PK)’. The research team applied Mixed-Method (Qualitative-Quantitative) with 16 families as respondents. The result of the research showed that there was a change in mean values of knowledge and attitude of family after applying health care interventions with P-value 0,001. This is directly proportional to the five family health tasks, the better knowledge and attitude of family about pulmonary tuberculosis disease, the better they understand health problem recognition, decision making, family health care, maintaining a conducive home environment and health facilities. Therefore, the implementation of family health care can improve and foster family health in preventing pulmonary tuberculosis disease.